Reduced Post-ischemic Brain Injury in Transient Receptor Potential Vanilloid 4 Knockout Mice - Tanaka, Koji; Matsumoto, Shoji; Yamada, Takeshi; Yamasaki, Ryo; Suzuki, Makoto; Kido, Mizuho A.; Kira, Jun-Ichi (Frontiers in Neuroscience, 2020)
Background and Purpose In the acute phase of ischemia-reperfusion, hypoperfusion associated with ischemia and reperfusion in microvascular regions and disruption of the blood–brain barrier (BBB) contribute to post-ischemic brain injury. We aimed to clarify whether brain injury following transient middle cerebral artery occlusion (tMCAO) is ameliorated in Transient receptor potential vanilloid 4 knockout (Trpv4-/-) mice. Methods tMCAO was induced in wild-type (WT) and Trpv4-/- mice aged 8–10 weeks. Ischemia-induced lesion volume was evaluated by 2,3,5-triphenyltetrazolium chloride staining at 24 h post-tMCAO. Tissue water content and Evans blue leakage in the ipsilateral hemisphere and a neurological score were evaluated at 48 h post-tMCAO. Transmission electron microscopy (TEM) was performed to assess the morphological changes in microvasculature in the ischemic lesions at 6 h post-tMCAO. Results Compared with WT mice, Trpv4-/- mice showed reduced ischemia-induced lesion volume and reduced water content and Evans blue leakage in the ipsilateral hemisphere alongside milder neurological symptoms. The loss of zonula occludens-1 and occludin proteins in the ipsilateral hemisphere was attenuated in Trpv4-/- mice. TEM revealed that parenchymal microvessels in the ischemic lesion were compressed and narrowed by the swollen endfeet of astrocytes in WT mice, but these effects were markedly ameliorated in Trpv4-/- mice. Conclusion The present results demonstrate that TRPV4 contributes to post-ischemic brain injury. The preserved microcirculation and BBB function shortly after reperfusion are the key neuroprotective roles of TRPV4 inhibition, which represents a promising target for the treatment of acute ischemic stroke.